The news interview : journalists and public figures on the air - Clayman, Steven; Heritage, John (Studies in interactional sociolinguistics, 2002)
This much-needed work examines the place of the news interview in Anglo-American society as well as its historical development. Through analyses of well-known interviews, the book explores the relationship between journalists and public figures, and reveals the tensions beneath the surface of the nightly news